Electoral Democracy and the Justice Imperative: Protecting Citizens’ Political Rights as a Human Rights Concern - Muhammad Mas Davit Herman Rudiyansah (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Electoral democracy is widely regarded as a fundamental mechanism for realizing popular sovereignty, yet its substantive quality is often undermined when justice and political rights are inadequately protected. This article examines electoral democracy through the lens of the justice imperative by positioning citizens’ political rights as an integral concern of the human rights regime. The study aims to analyze how principles of justice operate within electoral processes and to assess the extent to which elections function as instruments for the effective protection of political rights. Employing a normative-analytical approach grounded in human rights theory and democratic justice, the article critically engages with international human rights instruments, contemporary democratic theory, and relevant scholarly discourse. The analysis demonstrates that electoral democracy cannot be reduced to procedural compliance or periodic voting alone, but must be evaluated based on its capacity to ensure equal participation, non-discrimination, legal certainty, and meaningful representation. The findings reveal that deficiencies in electoral justice directly translate into violations of political rights, thereby weakening the legitimacy of democratic governance. This article argues that reframing electoral democracy within a human rights framework provides a more robust normative foundation for assessing electoral integrity and for strengthening the protection of citizens’ political rights. Such a perspective is essential for advancing justice-oriented democratic practices in contemporary constitutional and socio-political contexts. Demokrasi pemilihan umum sering dipahami sebagai instrumen utama perwujudan kedaulatan rakyat, namun kualitas substansialnya kerap melemah ketika prinsip keadilan dan perlindungan hak politik tidak dijalankan secara optimal. Artikel ini bertujuan menganalisis demokrasi elektoral dengan menempatkan imperatif keadilan sebagai fondasi normatif serta memposisikan hak politik warga negara sebagai bagian tak terpisahkan dari rezim hak asasi manusia. Kajian ini menggunakan pendekatan normatif-analitis dengan bertumpu pada teori keadilan, demokrasi, dan hak asasi manusia, serta menelaah instrumen HAM internasional dan wacana akademik kontemporer yang relevan. Hasil analisis menunjukkan bahwa demokrasi elektoral tidak dapat direduksi semata-mata pada kepatuhan prosedural atau pelaksanaan pemungutan suara secara periodik, melainkan harus diukur dari kemampuannya menjamin kesetaraan partisipasi, non-diskriminasi, kepastian hukum, dan representasi politik yang bermakna. Ketimpangan dalam keadilan pemilu terbukti berdampak langsung pada terlanggarnya hak politik warga negara dan pada akhirnya menggerus legitimasi demokrasi itu sendiri. Artikel ini menegaskan bahwa perumusan ulang demokrasi elektoral dalam kerangka hak asasi manusia memberikan dasar normatif yang lebih kokoh untuk menilai integritas pemilu sekaligus memperkuat perlindungan hak politik warga negara dalam konteks demokrasi kontemporer.